Reputasi KAP, Audit Tenure, Ukuran Perusahaan Klien dan Kualitas Audit (Studi pada Perusahaan LQ 45 Indonesia) - Komar Darya; Swasti Ayu Puspitasari (STIE Indonesia Banking School, 2017)
The purpose of this research is to investigate whether reputation of KAP, audit tenure, and the size of the client company associated to audit quality by using a proxy of discretionary accruals of the company in LQ 45 companies listed on the stock exchanges in Indonesia during 2011–2014. Purposive sampling is chosen as the sampling method of this study. Data obtained from secondary data in the annual reports of 19 companies listed on the Stock Exchange in 2011–2014. KAP reputation variables are measured through dummy Big four and non Big four, Audit tenure is measured through dummy rotation or not, while firm size is measured through the total natural logarithm of the asset. The results of this study indicate that the reputation of KAP has negative effect on audit quality, audit tenure and the size of the company’s client have positive effect on audit quality